ANALYZING THE IMPACT OF CRUDE PALM OIL PRICES ON STOCK MARKET RETURNS IN MALAYSIA - Norramadan, Nurul Raudhah; Mohamed, Suhana (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Crude palm oil (CPO) is a very important part of the Malaysian economy especially its role in export income, employment, and performance of capital market. The price changes in CPOs, as one of the major manufacturers of palm oil in the world, are significant to companies traded in Bursa Malaysia and stock market movements in general. This paper will review the correlation between stock market performance in Malaysia and the movement of crude palm oil prices between 2014-2024 based on a discussion-based approach. The paper, through a synthesis of the recent empirical and conceptual research, identifies the major transmission channels that link the changes in the CPO price to the stock market performance of the company in terms of profitability, macroeconomic factors, global market dynamics, and investor behaviour. The research adds to the body of knowledge by offering a comprehensive conceptual model that integrates some of the recent world occurrences like recovery in the aftermath of the pandemic and the volatility in commodity prices. The results can be of great help to the investors, as well as policy- makers and players in the market of emerging economies that rely heavily on commodities.